Glacial geomorphology in the Lunana area in the Bhutan Himalaya: Moraine stages, glacial lakes, and rock glaciers - Iwata, Shuji; Karma, Karma; Ageta, Yutaka; Sakai, Akiko; Narama, Chiyuki; Naito, Nozomu (Himalayan Journal of Sciences, 2008)
No abstract available